Solve the following equation for g: 2(g – h) = b + 4

Question

Solve the following equation for g: 2(g – h) = b + 4

in progress 0
Hailey 2 weeks 2021-09-12T01:08:11+00:00 1 Answer 0

Answers ( )

    0
    2021-09-12T01:09:25+00:00

    Answer:

    g = \frac{b+4+2h}{2}

    Step-by-step explanation:

    Given

    2(g – h) = b + 4 ← distribute parenthesis on left side

    2g – 2h = b + 4 ( add 2h to both sides )

    2g = b + 4 + 2h ( divide both sides by 2 )

    g = \frac{b+4+2h}{2}

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )